The Role of Market Iraq Securities in activation Industrial sector Special - بريهي فارس كريم; فاضل طيف عباس (Journal of Economics and Administrative Sciences, 2018)
The financial market plays an important role in influencing the economic sectors, including the private industrial sector, through the provision of capital and transfer from savers to investors for the purpose of establishing or expanding projects. Therefore, the financial market is one of the important tools in stimulating the economy in general and the industrial sector in particular, Through the inclusion of industrial companies in the financial market and the introduction of industrial shares to the public, and then provide the necessary funding to stimulate the private industrial sector, Iraq is one of the oil-dependent countries on the oil sector mainly, which lacks industrial production, which is from Are the sectors that lead to economic recovery and increase the gross domestic product. There are several factors that led to the deterioration of industrial production in Iraq, including the frequent wars and the deterioration of infrastructure and the low funding resources necessary to revive it and the dependence on the main import and thus compete with local goods, so the financial market is an important tool For the financing of the private industrial sector, where it was shown through the practical application of the study and using the model of self-regression of distributed delay periods (ARDL) that there is a significant positive correlation and long-term relationship between the variables of the Iraqi market for securities and int C, the development of the Iraqi market for securities and increasing the inclusion of industrial companies lead to an increase in industrial production and thus improve the level of economic activity, and increasing the market value, the number of contracts and the number of industrial shares in the Iraqi market for securities lead to increase industrial production of private, The increase in trading volume leads to lower industrial production.